Northrop Frye and American fiction - Le Fustec, Claude (Frye studies., 2015)
Claude Le Fustec presents insightful readings of the presence of transcendence and biblical imagination in canonical novels by American writers ranging from Nathaniel Hawthorne to Toni Morrison.